Analogues of 2′-hydroxychalcone with modified C4-substituents as the inhibitors against human acetylcholinesterase. (1st January 2021) - Sukumaran, Sri Devi; Nasir, Shah Bakhtiar; Tee, Jia Ti; Buckle, Michael J. C.; Othman, Rozana; Rahman, Noorsaadah Abd.; Lee, Vannajan Sanghiran; Bukhari, Syed Nasir Abbas; Chee, Chin Fei
Abstract: A series of C4-substituted tertiary nitrogen-bearing 2′-hydroxychalcones were designed and synthesised based on a previous mixed type acetylcholinesterase inhibitor. Majority of the 2′-hydroxychalcone analogues displayed a better inhibition against acetylcholinesterase (AChE) than butyrylcholinesterase (BuChE). Among them, compound 4c was identified as the most potent AChE inhibitor (IC50 : 3.3 µM) and showed the highest selectivity for AChE over BuChE (ratio >30:1). Molecular docking studies suggested that compound 4c interacts with both the peripheral anionic site (PAS) and catalytic anionic site (CAS) regions of AChE. ADMET analysis confirmed the therapeutic potential of compound 4c based on its blood–brain barrier penetrating. Overall, the results suggest that this 2′-hydroxychalcone deserves further investigation into the therapeutic lead for Alzheimer's disease (AD). GRAPHICAL ABSTRACT: UF0001